Backstepping Design of Robust Output Feedback Regulators for Boundary Controlled Parabolic PDEs - Deutscher, Joachim (IEEE Transactions on Automatic Control, 2016)
In this article a backstepping-based solution of the robust output regulation problem for boundary controlled parabolic PDEs with spatially varying parameters is presented. This is achieved by stabilizing the plant extended with a finite-dimensional internal model of the exogenous signals. For the resulting PDE-ODE system with spatially varying parameters a systematic backstepping-based compensator design method is developed. The robustness of the achieved output regulation is verified for non-destabilizing model uncertainties. An uncertain parabolic system illustrates the results of the articl
Keywords: Backstepping; boundary control; linear distributed-parameter systems; parabolic systems; robust output regulation